DEVELOPMENT OF ADMINISTRATIVE RESOURCES IN THE IMPLEMENTATION OF E-GOVERNMENT IN THE ADMINISTRATIVE DEVELOPMENT BUREAU OF THE EAST JAVA PROVINCIAL SECRETARIAT - Ilham Try Atmaja (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2023)
The East Java Provincial Government in the implementation of E-Government is also proven by the issuance of the East Java the Surat Keputusan Gubernur No. 188/126/KPTS/013/2022 on the Coordination Team for Electronic Based Government Systems of the East Java Province in 2022, which has the task of providing recommendations for the direction of development of information and communication technology and coordinating the implementation of Electronic Based Government Systems (SPBE) in the East Java Provincial Government. However, from the observations made, it appears that the development of employees in the Administration Development Bureau of the East Java Provincial Secretariat has not fully progressed as expected. The purpose of this study is to identify and analyze the development of Human Resources and the barriers to the implementation of E-Government in the Administration Development Bureau of the East Java Provincial Secretariat. The researcher uses a qualitative research method. The focus of this study is on the development of Human Resources in the Administration Development Bureau of the East Java Provincial Secretariat. The research instrument is interviewing. The informants in this study are the Administration Development Bureau of the East Java Provincial Secretariat, the Head of the Administration Sub-Division, and the Functional Officials and Staff at the Administration Development Bureau of the East Java Provincial Secretariat. The results show that the development of Human Resources is still not given enough attention by the Administration Development Bureau of the East Java Provincial Secretariat, as seen from the low interest of employees (staff) in carrying out new things, especially in education and training and the lack of ability to think or reason/logic to optimize applications, resulting in the lack of optimal performance from the employees.